The let them theory : a life-changing tool that millions of people can't stop talking about - Robbins, Mel, 1968- (New Delhi: Hay House India, 2024)
"If you've ever felt stuck, overwhelmed, or frustrated with where you are, the problem isn't you. The problem is the power you give to other people. Two simple words--Let Them--will set you free. Free from the opinions, drama, and judgments of others. Free from the exhausting cycle of trying to manage everything and everyone around you. The Let Them Theory puts the power to create a life you love back in your hands--and this book will show you exactly how to do it. [Robbins] teaches you how to stop wasting energy on what you can't control and start focusing on what truly matters: YOU. Your happiness. Your goals. Your life. Using the same no-nonsense, science-backed approach that's made The Mel Robbins Podcast a global sensation, Robbins explains why The Let Them Theory is already loved by millions and how you can apply it in eight key areas of your life to make the biggest impact" --
Introduction: My story -- The let them theory -- You and the let them theory. Managing stress ; Fearing other people's opinions ; Dealing with someone else's emotional reactions ; Overcoming chronic comparison -- Your relationships and the let them theory. Mastering adult friendship ; Motivating other people to change ; Helping someone who is struggling ; Choosing the love you deserve -- Conclusion: Your let me era is here -- Appendix.
Includes bibliographical references (pages 311-322).
Keywords: Self-actualization (Psychology); Choice (Psychology); Control (Psychology); Self-management (Psychology); Conduct of life; Self-talk.; Success; ethics (philosophical concept); BUSINESS & ECONOMICS / Personal Success; Self-actualization (Psychology); Success; Self-talk; Self-realization.; Success; Self-help techniques; Self-help publications; Self-help publications